2008
DOI: 10.1002/ana.21518
|View full text |Cite
|
Sign up to set email alerts
|

Seizures and reproductive function: Insights from female rats with epilepsy

Abstract: OBJECTIVE-Chronic seizures in women can have adverse effects on reproductive function, such as polycystic ovarian syndrome (PCOS), but it has been difficult to dissociate the effects of epilepsy per se from the role of antiepileptic drugs (AEDs). To distinguish the effects of chronic seizures from AEDs, we used the laboratory rat, where an epileptic condition can be induced without concomitant AED treatment.METHODS-Adult female rats were administered the chemoconvulsant pilocarpine to initiate status epileptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
2
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 65 publications
4
48
2
6
Order By: Relevance
“…Pilocarpine epileptogenesis leads to obesity in rodents (Scharfman et al, 2008; Ruiz et al, 2011) and a similar phenomenon has been described in patients with epilepsy (Daniels et al, 2009). In the present study, SE+Veh mice exhibited a significant 35% increase in body weight over the course of the experiment (p<0.001, one-way RM ANOVA).…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…Pilocarpine epileptogenesis leads to obesity in rodents (Scharfman et al, 2008; Ruiz et al, 2011) and a similar phenomenon has been described in patients with epilepsy (Daniels et al, 2009). In the present study, SE+Veh mice exhibited a significant 35% increase in body weight over the course of the experiment (p<0.001, one-way RM ANOVA).…”
Section: Resultssupporting
confidence: 58%
“…Pilocarpine status epilepticus leads to obesity in rodents (Scharfman et al, 2008; Ruiz et al, 2011). Obesity is also a common comorbidity of human epilepsy (Ladino et al, 2014; Janousek et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In kindling, for example, females often develop persistent estrus (Edwards et al, 1999) where a high level of estrogen develops chronically. Irregular estrous cycles typically occur in models of TLE that use SE as the initial insult (Amado and Cavalheiro, 1998; Scharfman et al, 2008). Polycystic ovaries and increased androgen levels can develop, adding additional experimental factors (Scharfman et al, 2008).…”
Section: Seizures Epileptogenesis and Epilepsy In Rodentsmentioning
confidence: 99%
“…Irregular estrous cycles typically occur in models of TLE that use SE as the initial insult (Amado and Cavalheiro, 1998; Scharfman et al, 2008). Polycystic ovaries and increased androgen levels can develop, adding additional experimental factors (Scharfman et al, 2008). Although interesting because women with epilepsy can develop polycystic ovaries and increased androgen levels, it is difficult to use laboratory animals to explore sex differences in epileptogenesis because inducing convulsive seizures causes a loss or dramatic alteration in normal gonadal hormones.…”
Section: Seizures Epileptogenesis and Epilepsy In Rodentsmentioning
confidence: 99%
“…Reproductive anomalies and high levels of luteinizing hormone (LH) and altered LH: follicule-stimulating hormone (FSH) ratio have been reported in epileptic women (6). Besides, Scharfman et al demonstrated that an epileptic condition in the rat leads to increased body weight, cystic ovaries and elevated testosterone levels (7).…”
Section: Introductionmentioning
confidence: 98%